PENGARUH KOMPRES HANGAT TERHADAP PENURUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI RUMAH SAKIT UMUM IMELDA PEKERJA INDONESIA MEDAN TAHUN 2022 - Magdalena T. Bolon, Christina; Manurung, Nixson Manurung; Manurung, Rostinah; Dewi, Ratna; Siregar, Sarmaida; Buulolo, Barzilai (Jurnal Ilmiah Keperawatan IMELDA, 2023)
Hypertension is often called the "silent killer" because hypertension sufferers often never experience health problems due to the disease they suffer from. Hypertension or high blood pressure is a chronic condition characterized by increased blood pressure on the walls of the arteries. The initial symptoms of hypertension are usually asymptomatic, only characterized by an increase in blood pressure. The aim of this research is to find out whether there is an effect of giving warm compresses on reducing hypertension. This research method uses a quasi experiment by giving warm compresses to hypertension sufferers. The sample used in this research was 36 people using purposive sampling technique. Inclusion criteria were willing to become participants, sufferers suffering from grade 1 hypertension, communicative and cooperative, no other comorbidities. The instruments created were demographic sheets and observation sheets and were analyzed univariately and bivariately. With the Wilcoxon test, the p-value was 0.01 (P-value <0.05). It can be concluded that the effect of warm compresses on reducing blood pressure in patients can be used to prevent stroke and improve health in the community.